Exciton dynamics in ZnSe/ZnSxSe1-x superlattices - Dabbicco, M; Stevens, C; Adams, R; Taylor, R; Ryan, J; Cingolani, R; Suemune, I (1995)
Time-resolved photoluminescence experiments in a wide carrier density range up to and beyond the threshold for stimulated emission in ZnSe/ZnSxSe1-x. superlattices are presented. Different localisation mechanisms of free excitons are identified giving rise to different radiative recombination channels. At high carrier density localised energy states merge into miniband that allows for exciton-exciton interaction, such as screening of the free-exciton absorption and inelastic exciton-exciton scattering.